Comparison of lycopene, β-carotene and phenolic contents of tomato using conventional and ecological horticultural practices, and arbuscular mycorrhizal fungi (amf) (2008)
Tomato fruits are rich in anti-oxidant compounds that have been recognized as benef icial for human health. Horticultural practices can influence the concentration of these secondary metabolites. Arbuscular mycorrhizal fungi (AMF) can increase nutrient and water absorption of plants. The experiment, performed under glasshouse, examined whether organically grown ‘Vitella F1’ tomatoes differed in their fruit content of lycopene, β- carotene and total phenols from that found in conventionally grown tomatoes. Treatments were the cultivation methods: conventional, organic, conventional+AMF and organic+AMF. When comparing the cultivation method, no significant differences for the analyzed nutritional parameters were found; only tomatoes grown organically had slightly lower total phenolic contents. In both cultivation methods, tomato plants inoculated with AMF (Glomus sp.) built higher lycopene content in fruits than those without inoculation. Organic grown tomatoes increased β-carotene and total phenolic contents in fruits as a result of the AMF treatment. AMF applications increased root fresh weight but not shoot fresh weight. The improved growth and nutrient acquisition in tomato demonstrated the potential of AMF colonization for increased antioxidant compounds in fruits. White fly (Trialeurodes vaporariorum) was controlled successfully with application of diatomaceous earth Fossil Shield® 90 in organic treatments as well as with Applaud® in the conventional cultivation methods.